Border ecologies Hong Kong's mainland frontier - Bolchover, Joshua (Birkhauser, 2017)
Hong Kong's border with Shenzhen is dissolving. By 2047, the border will likely not exist. Integration with the Mainland will remove distinctions created by the 'one country two systems' policy. The uncertainty surrounding what will happen has created anxiety relating to law, identity, freedom of speech, and voting rights. Caught in this debate is the Frontier Closed Area, a buffer zone created by the British in 1951 and an inaccessible landscape of eco-systems including tidal estuaries, fish farms, primary forests, historic villages and abandoned military posts. In contrast, Shenzhen, poster-child of China's economic reform era, has exploded into a metropolis of 15 million plus. The book explores this unique border ecology that evolved as Hong Kong and the Mainland transformed. Design strategies inserted within this ecology promote alternate forms of development. ... The example widens the discourse on borders to raise critical issues that impact the contemporary city."